Market power assessment and mitigation in hydrothermal systems. - Kelman, R. (IEEE Transactions on power systems)
The objective of this work is to investigate market power issues in bid-based hydrothermal scheduling. Initially, market power is simulated with a single stage Nash-Cournot equilibrium model. Market power assessment for multiple stages is then carried through a stochastic dynamic programming scheme. The decision in each stage and state is the equilibrium of a multi-agent game. Thereafter, mitigation measures, especially bilateral contracts, are investigated. Case studies with data taken from the Brazilian system are presented and discussed